Opportunity of nutritional support. Morbility and mortality in surgical cancer patient. - Bertullo, Hugo; Olano, Estela; Giangrossi, Mario; Duarte, Gladys; Barrial, Neldi; Imperial, Olga (Cirugía del Uruguay, 1987)
25 neoplasic surgical patients with similar canear extension and surgical visceral resection, were asses